A review of digital serious games for tsunami risk communication - HAWTHORN, Steven (2021)
The research conducted a thorough review of evidence and effectiveness of digital serious games (SGs) for communication of action-oriented key messages (related to tsunami evacuation) to children. Significant scientific research investigates tsunami risk which is not always effectively communicated to children who are expected to make appropriate decisions during a tsunami event. SGs can motivate children and enhance risk communication. Computing technologies offer a delivery platform to access digital SGs which require little educator training and motivate learners. The research reviewed evidence of effective SGs that address tsunami risk and are deployable by educators. Based on this review, it is evident that very few suitable classroom deployable, digital SGs that address tsunami evacuation decision-making are available. Results showed only 2 suitable, available games. Similarly, while general evidence of the effectiveness of digital SGs was found, the evaluation of and evidence for the specific effectiveness of the available games was extremely limited. The education establishment and disaster community could exploit SG technology more effectively to communicate natural hazard risk to children in a global context where such risk is increasing. The research informs future game development projects which need to embrace comprehensive stakeholder involvement and inputs. Recommendations for serious game development projects are proposed.